Alternative therapy for teeth with mineralized pulp cavity in aesthetic áreas using immediate implant KEAGUIDE system: case report (Research, Society and Development, 2021)
Complete mineralization of the pulp cavity can occur due to numerous factors, such as trauma and association with orthodontic treatment. Subsequent impacts to this event can make conventional endodontic treatment impracticable, leading to secondary approaches as dental implants. In this clinical case, the KEAGUIDE system method was used. This work is justified due to the importance of distinguishing the possible post-trauma treatment routes and the relevance of the presence of the previous esthetic sector, in addition to the interference of tooth loss in the stomatognathic system. The objective was to describe a clinical case of a 20 years old female patient with historical trauma on teeth 11 and 21, in which the case evolution leaded to necessity of atraumatic extractions and installation of guided implants. After a detailed anamnesis, image examination and approval by the Research Ethics Committee, a clinical description and a qualitative research were fulfilled, which aimed to deepen whithin the topic, contributing to the collection of information. It was concluded that the design of post trauma treatment must be individualized. Furthermore, the choice of surgical technique favored positive results for the patient’s esthetics and rehabilitation.